Impact of Oil Prices on Stock Markets in Major Latin American Countries (2000-2015) - Santillán-Salgado, Roberto; Calderón-Villarreal, Cuauhtémoc; Venegas-MartÃnez, Francisco (International Journal of Energy Economics and Policy, 2017)
This paper studies how sensitive are the stock market returns of Argentina, Brazil, Chile, Colombia, Mexico, and Peru to international oil price fluctuations (West Texas Intermediate). A Panel Data analysis with a Random Effects model, using the world stock market index (MSCWI), domestic money market rates, and currency exchange rates as control variables suggests that, after controlling for the individual countries non-observed characteristics, oil prices explain positively monthly returns of the stock markets. The rest of the control variables have the desired sign and statistical significance; the sample data includes monthly observations from 2000 to 2015. The main finding of this research is that it does not matter if countries are exporters (Brazil, México, Venezuela, Colombia and Argentina) or importers (Peru and Chile) of oil, in the region as a whole, an increase of oil prices has a positive effect on stock returns. Keywords: Oil prices, stock market, panel data analysis, Latin America. JEL Classifications: N26, C33, Q42.